2011
DOI: 10.1111/j.1747-0285.2011.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Curcumin Analogue Dimethoxycurcumin with DNA

Abstract: Dimethoxycurcumin (Dimc), a synthetic analogue of curcumin, that has been reported to exhibit better in vivo stability and anti-tumour activity, was investigated for its interaction with DNA, employing spectroscopic methods based on absorption, fluorescence, circular dichroism (CD), ethidium bromide (EtBr) competitive binding assay, 4'-6-diamidino-2-phenylindole (DAPI) displacement assay and fluorescence resonance energy transfer (FRET) assay. The mean binding constant for its interaction with calf thymus DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…DAPI is an established minor groove binder of double-stranded B-DNA (Kunwar et al, 2011;Larsen, Goodsell, Cascio, Grzeskowiak, & Dickerson, 1989;Zaitsev & Kowalczykowski, 1998). However, in the presence of another minor groove-binding molecule, there could be competition between the new molecule and DAPI for binding to the minor groove, thereby resulting in quenching of the fluorescence intensity of the DAPI-DNA complex.…”
Section: Minor Groove Displacement Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…DAPI is an established minor groove binder of double-stranded B-DNA (Kunwar et al, 2011;Larsen, Goodsell, Cascio, Grzeskowiak, & Dickerson, 1989;Zaitsev & Kowalczykowski, 1998). However, in the presence of another minor groove-binding molecule, there could be competition between the new molecule and DAPI for binding to the minor groove, thereby resulting in quenching of the fluorescence intensity of the DAPI-DNA complex.…”
Section: Minor Groove Displacement Assaymentioning
confidence: 99%
“…Minor groove displacement assay was carried out in fluorescence with two well-established minor groove binders, DAPI (4',6-diamidino-2-phenylindole) and Hoechst 33258, using protocols reported in the literature (Basu & Kumar, 2013a, 2014Kunwar et al, 2011;Sahoo, Ghosh, Bera, & Dasgupta, 2008;Zaitsev & Kowalczykowski, 1998). All the fluorescence measurements were performed on a Shimadzu RF-5301PC spectrofluorimeter (Shimadzu Corporation, Kyoto, Japan).…”
Section: Minor Groove Displacement Assaymentioning
confidence: 99%
“…DMCU derivatives effectively inhibited the phosphorylation of signal transducer and activator of transcription 3 (STAT3), exhibited DNA-binding activities [10,11], and inhibited the 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced activation of the activator protein-1 (AP-1) [12]. Although the interaction of CU and its derivatives with DNA have been studied, the interactions between DNA and CU analogs with broken α, β-unsaturated diketone structures have not been explored so far [13][14][15][16]. Thus, it is pertinent to investigate the reaction modes and kinetic mechanisms between DMCU and DNA to reveal how this compound may be modified to improve its biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 5a, b, interactions with both boron compounds decrease the intensities of CD values at 245 and 275 nm, and no consistent change at 220 is observed, which may indicate that the right-handed helicity of B-DNA is modified [27] with slight changes in the base stacking interactions. Since there is no peak shift in the spectra of both samples and no increase in the intensity at 275 nm is observed, the changes in the CD spectra are not indicative for a B to A conformational transition.…”
Section: Spectramentioning
confidence: 87%
“…It is reported that the peak at 275 nm corresponds to base stacking, and the peak at 245 nm corresponds to polynucleotide helicity of DNA [27]. In addition, a red shift at 220 nm and an intensity increase at 275-nm peaks are some of the characteristics for B to A conformational change [28].…”
Section: Spectramentioning
confidence: 99%